Early Bronze Age in Western Anatolia - Harrison, Laura K., 1985-; Bilgen, A. Nejat; Kapuci, Asuman, 1982-; University of Buffalo. Institute for European and Mediterranean Archaeology (Albany : State University of New York Press, 2021)
Examines the culture and chronology of increasingly complex urban societies in western Anatolia during the Early Bronze Age.
Distribution Area and Chronology of the Volute Vessels -- Conclusion -- Acknowledgments -- Note -- References Cited -- Catalogue -- Chapter Seven Küllüoba Early Bronze Age III Pottery -- Conclusion -- References Cited -- Chapter Eight The Figurine/Idol Types of Western Anatolia in the Early Bronze Age and Their Relationship with Cultural Regions -- The Troy-Yortan Cultural Region -- The Bithynian Cultural Region -- The Phyrigian Cultural Region -- The Büyük Menderes-Upper Porsuk Cultural Region -- The Lycian-Pisidian Cultural Region
eBooks on EBSCOhost
Keywords: Turkey -- Antiquities; Excavations (Archaeology) -- Turkey; Bronze age -- Turkey; Material culture -- Turkey -- History; Human settlements -- Turkey -- History; Turkey -- History -- To 1453.; Archaeological dating -- Turkey; Turquie -- Antiquités.; Asie Mineure -- Histoire; SOCIAL SCIENCE / Archaeology; Antiquities; Archaeological dating; Bronze age; Excavations (Archaeology); Human settlements; Material culture; Turkey; To 1453; History